2015
DOI: 10.1111/1462-2920.12900
|View full text |Cite
|
Sign up to set email alerts
|

Early rhizosphere microbiome composition is related to the growth and Zn uptake of willows introduced to a former landfill

Abstract: Although plants introduced for site restoration are pre-selected for specific traits (e.g. trace element bioaccumulation, rapid growth in poor soils), the in situ success of these plants likely depends on the recruitment of appropriate rhizosphere microorganisms from their new environment. We introduced three willow (Salix spp.) cultivars to a contaminated landfill, and performed soil chemical analyses, plant measurements, and Ion Torrent sequencing of rhizospheric fungal and bacterial communities at 4 and 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 71 publications
2
38
1
Order By: Relevance
“…Diverse root-exudate production in the rhizosphere could also result in the increased ␣-diversity of bacteria in the soils revegetated with S. bebbiana and V. myrtilloides. Both plants can develop symbiotic relationships with fungi: ectomycorrhizae with S. bebbiana and ericoid mycorrhizae with V. myrtilloides (61)(62)(63). Willows associate with specific ectomycorrhizal fungi, which, once established, increase bacterial diversity in the soil (62).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diverse root-exudate production in the rhizosphere could also result in the increased ␣-diversity of bacteria in the soils revegetated with S. bebbiana and V. myrtilloides. Both plants can develop symbiotic relationships with fungi: ectomycorrhizae with S. bebbiana and ericoid mycorrhizae with V. myrtilloides (61)(62)(63). Willows associate with specific ectomycorrhizal fungi, which, once established, increase bacterial diversity in the soil (62).…”
Section: Discussionmentioning
confidence: 99%
“…Both plants can develop symbiotic relationships with fungi: ectomycorrhizae with S. bebbiana and ericoid mycorrhizae with V. myrtilloides (61)(62)(63). Willows associate with specific ectomycorrhizal fungi, which, once established, increase bacterial diversity in the soil (62). Willows also produce a small, but highly labile pool of organic carbon that can support abundant copiotrophic proteobacteria (64).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, when associated with endomycorrhizal fungi, poplars exhibit enhanced tolerance to biotic and abiotic stress, with better growth and higher biomass production (Cicatelli et al, 2014). When plants are introduced for site restoration, the in-situ success of these plants will likely be depending on the recruitment of appropriate rhizosphere microorganisms from their new environment (Bell et al, 2015). In a recent study, we demonstrated that the occurrence and persistence of ectomycorrhizal symbionts were greatly driven by site characteristics (Foulon et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work into the human microbiome is proving an essential element in health research (Gill et al, 2006;Turnbaugh et al, 2007;Nelson et al, 2010;Davids et al, 2016), particularly concerning bacterial diversity within gastrointestinal studies. Such diversity in the microbiome is now well established as an essential factor in root-soil interactions, often termed the rhizosphere (Luo et al, 2009;He et al, 2013;Sullivan et al, 2013;Yergeau et al, 2014;Bell et al, 2015;de Vrieze, 2015). Less work has extended the metaorganism beyond bacteria, or singular target pathogens, herbivores, or symbiotes.…”
mentioning
confidence: 99%